3D echocardiography derived reference values and determinants of left ventricular twist and torsion from the population-based STAAB cohort study - Julia Napp; Götz Gelbrich; Floran Sahiti; Vladimir Cejka; Dora Pelin; Lena Schmidbauer; Mengmeng Chen; Niklas Hitschrich; Marcus Schreckenberg; Stefan Frantz; Peter U. Heuschmann; Stefan Störk; et al. (Scientific Reports)
Abstract Left ventricular (LV) rotational function parameters provide in-depth information about LV mechanical function as well as prognostic information. Using three-dimensional (3D) echocardiography, we identified determinants of LV “twist” and “torsion”, and established reference values using a large population-based cohort. 3D echocardiography images were recorded in n = 2803 subjects within the prospective STAAB cohort study investigating a representative age- and sex-stratified sample of residents of the city of Würzburg, aged 30–79 years, without history of heart failure. Valid 3D image analysis was performed in n = 1831 (65.3%) subjects (mean age 57 ± 11 years, 49.3% women). Using general linear models, we identified determinants of LV twist and torsion: there was a positive association between LV rotational parameters and age, female sex, and blood pressure but a negative association with body weight. From a subset of 479 apparently healthy individuals exhibiting no cardiovascular (CV) risk factors or CV disease (mean age 52 ± 10 years, 56.4% women), we derived reference percentiles for twist and torsion. LV rotation is determined by a complex interplay of sub-endocardial and sub-epicardial fibers which might be affected differentially by potential risk factors. We found a differential association with respective determinants as LV rotational parameters increased with age and with higher blood pressure but decreased with higher body weight. Further research is needed to elucidate these associations in more detail and to determine the additional information contributed by twist and torsion. To facilitate respective attempts and to set an individual’s results in relation to a population-based reference, we derived normal values for twist and torsion from a sub-collective of healthy individuals.